2000
DOI: 10.1097/00000542-200012000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Ventilation on Release of Cytokines into Systemic Circulation in Patients with Normal Pulmonary Function

Abstract: Initiation of mechanical ventilation for 1 h in patients without previous lung injury caused no consistent changes in plasma levels of studied mediators. Mechanical ventilation with high V(T) on ZEEP did not result in higher cytokine levels compared with lung-protective ventilatory strategies. Previous lunge damage seems to be mandatory to cause an increase in plasma cytokines after 1 h of high V(T) mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
126
7
22

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 230 publications
(162 citation statements)
references
References 27 publications
5
126
7
22
Order By: Relevance
“…The results of these studies have been mixed, with some investigators showing increases in serum and bronchoalveolar lavage markers of injury 10,[13][14][15][16]19 whereas others have not. 11,12,17,18 There have been remarkably few trials examining clinical outcomes associated with low tidal volume ventilation strategies in otherwise healthy populations. In 1990, Lee et al 29 randomly assigned 103 surgical ICU patients to ventilation with 6 vs. 12 ml/kg tidal volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies have been mixed, with some investigators showing increases in serum and bronchoalveolar lavage markers of injury 10,[13][14][15][16]19 whereas others have not. 11,12,17,18 There have been remarkably few trials examining clinical outcomes associated with low tidal volume ventilation strategies in otherwise healthy populations. In 1990, Lee et al 29 randomly assigned 103 surgical ICU patients to ventilation with 6 vs. 12 ml/kg tidal volume.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite biologic plausibility and considerable retrospective data to support limiting tidal volume in all ventilated patients, equipoise remains regarding optimal tidal volume in non-ALI patients. Although various groups of surgical patients, but especially cardiac surgical patients, have been observed, [8][9][10][11][12][13][14][15][16][17][18][19][20] these investigations have focused primarily on surrogate outcomes measures, leaving a lack of clarity regarding optimal perioperative ventilator strategy.…”
mentioning
confidence: 99%
“…Local and systemic infl ammatory biomarkers, including IL-8, IL-1, IL-6, IL-10, TNF-α and IL-12, were determined after 3 hours of mechanical ventilation [22]. Both studies were unable to fi nd any signifi cant diff erences in terms of infl ammatory mediators and the authors concluded that, in contrast to patients with acute lung injury in whom there is a systemic infl ammatory reaction during major surgery, in uninjured normal lungs short term mechanical ventilation alone with high V T levels did not increase pulmonary or systemic infl ammation related to surgery [21], [22]. No diff erences in biomarkers of lung epithelial injury were observed after 5 hours in a later study, which compared ventilation with V T 12 ml/kg ideal body weight without PEEP versus V T 6 ml/kg and PEEP 10 cmH 2 O [23].…”
Section: Abdominal Surgerymentioning
confidence: 98%
“…In this context, Wrigge and colleagues investigated in two studies the eff ect of diff erent ventilatory strategies on the release of infl ammatory mediators in patients undergoing elective surgery [21], [22]. In the fi rst study, 39 patients scheduled for extra-thoracic surgery (abdominal, vascular, bone and other) were randomized to one of three mechanical ventilation strategies: 1) V T of 15 ml/kg ideal body weight without PEEP; 2) V T of 6 ml/ kg without PEEP; and 3) V T of 6 ml/kg with PEEP 10 cmH 2 O.…”
Section: Abdominal Surgerymentioning
confidence: 99%
See 1 more Smart Citation